Acute Haemoperitoneum: an unusual presentation of choriocarcinoma - Nargis, Nazlima; Karim, Md Iqbal; Khuldhon, Abu M (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Choriocarcinoma is a highly malignant epithelial tumour arising from the trophoblastic tissue. It commonly occurs in women of reproductive age, rarely in post-menopausal women and in women under 20 years of age. Methods: The case was initially diagnosed as an unusual presentation of choriocarcinoma with acute haemoperitoneum due to perforation of uterus with lung metastasis. The patient an 18 yr old woman came with acute abdominal pain and signs of haemoperitoneum. Emergency laparotomy followed by hysterectomy was done. Subsequently patient took chemotherapy and improved. Conclusion: Acute haemoperitoneum is a medical emergency. So this case report emphasizes the need of sophisticated diagnostic technology for early diagnosis and successful management of the patient. Clinician should give more attention to unusal presentation of choriocarcinoma. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21850 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013